Paraneoplastic retinopathy associated with retroperitoneal liposarcoma - Mineo Kondo (Dove Medical Press, 2010)
Mineo Kondo1, Kumiko Mokuno2, Ai Uemura1, Shu Kachi1, Makoto Nakamura1, Atsuya Kondo3, Hiroko Terasaki11Department of Ophthalmology, Nagoya University Graduate School of Medicine, Nagoya, Japan; 2Department of Ophthalmology, 3Department of Urology, Kariya Toyota General Hospital Kariya, JapanAbstract: We report a case of paraneoplastic retinopathy associated with a retroperitoneal liposarcoma. A 42-year-old man was referred to our hospital with complaints of night blindness and blurred vision in the peripheral field. Electroretinograms showed a progressive amplitude reduction in his both eyes. Abdominal magnetic resonance imaging showed a large retroperitoneal mass, and pathologic examination revealed a dedifferentiated liposarcoma. Western blot analysis showed an antiretinal antibody in the serum of our patient, and his serum reacted with the photoreceptors of a bovine retina. To the best of our knowledge, this is the first case of paraneoplastic retinopathy associated with a liposarcoma.Keywords: paraneoplastic retinopathy, retroperitneal liposarcoma, electroretinogram, cancerassociated retinopathy